Potential of Hidrogen (pH) Saliva Sebelum dan Sesudah Berkumur dengan Yoghurt - Sa'adah, Nikmatus; Soendoro, Mahayatma; Wahyuningsih, Ida; Mashudi, Thoifur (Universitas Nusantara PGRI Kediri, 2020)
Currently, there are many foods which contain cariogenic material among others are sugars and other sweet foods. These cariogenic foods will decrease the pH of saliva. The pH of saliva is one of the important factors that can affect the process of demineralization on the surfaces of the teeth. Streptococcus mutans is microorganism can be the main cause of caries. Probiotic bacteria can prevent and decrease the incident of dental caries or tooth decay and work directly on the Streptococcus mutans as cariogenic bacteria. Yogurt is a food produced by probiotic bacterial fermentation of milk. Yogurt has a high buffer capacity, it does not cause erosive, and it has a low cariogenic potential. Based on the background of the study, the writer is interested to conduct a study about the salivary pH before and after gargling with yogurt and kefir. Method: The research design was pre-experimental using pre and post-test group design. The samples consist of 27 people. Results: The data results of yogurt group was analyzed using parametric Paired T-Test with a significant value of 0,000, which means that there was significant difference between the groups before and after gargling with yogurt. Conclusion: There is a difference of the pH of saliva before and after gargling with yogurt.